An Analysis of Language Styles Used by Burger King on Instagram Posts - Eka Desya Rahmadany; Nur Muthmainnah Halim; Djaenab Djaenab (Tamaddun Life, 2021)
This study aims to: 1.) find out the style of language in the post on the Burger King Instagram page. 2.) find out what style of language is the most dominant used by Burger King. The study method used in this study is descriptive qualitative method. The present study used Instagram social media of Burger King which is American in an Indonesian branch. The study found 20 captions on posts on Instagram Burger King. The study aims to analyze the data by looking for images that possessed captions, then classifying the data based on language styles such as frozen style, formal style, casual style, consultative style, and also intimate style. The results of this study varied widely. There were 13 kinds of casual style and 13 kinds of consultative style, then followed by 5 kinds of formal style and 6 kinds of intimate style. While the frozen style was not found on the American and Indonesian Burger King Instagram because the language style used was very standard. Based on the results of data analysis and discussion, it was found that the most dominant language style used was casual style and consultative style for their advertising. Casual style is a style of language that uses a mixture of language and language elements used were very relaxed in nature, while consultative style is a style of business language because it talks or relates about business. This style of language is the most dominant to increase consumer interest in buying the product.